2005
DOI: 10.1159/000085032
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of CA125 as an Index of Peritoneal Mesothelial Cell Mass

Abstract: Background: CA125 is commonly used as an index of the mesothelial cell mass in patients treated with peritoneal dialysis. However, we have no data that show a direct relationship between the number of mesothelial cells, their functional properties, and the amount of CA125 produced in these cells. Methods: Experiments were performed on primary in vitro cultures of human peritoneal mesothelial cells obtained from 32 donors of various ages and of both sexes. Spontaneous release of CA125 from the confluent mesothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 33 publications
(20 reference statements)
1
27
1
Order By: Relevance
“…CA-125 is usually measured in solution biocompatibility studies, and it was also recommended as a tool for longitudinal membrane status evaluation. Although Breborowicz et al [27] reported limitations of CA-125 as an index of peritoneal mesothelial cell mass[,] they demonstrated a reduction of CA-125 secretion and expression with chronic exposure to glucose solutions. VEGF is spontaneously produced by cultured human mesothelial cells [21], but also by a variety of other cells, like vascular smooth muscle cells [28].…”
Section: Discussionmentioning
confidence: 99%
“…CA-125 is usually measured in solution biocompatibility studies, and it was also recommended as a tool for longitudinal membrane status evaluation. Although Breborowicz et al [27] reported limitations of CA-125 as an index of peritoneal mesothelial cell mass[,] they demonstrated a reduction of CA-125 secretion and expression with chronic exposure to glucose solutions. VEGF is spontaneously produced by cultured human mesothelial cells [21], but also by a variety of other cells, like vascular smooth muscle cells [28].…”
Section: Discussionmentioning
confidence: 99%
“…Although this has been recently questioned [31] , the finding of low levels of effluent CA125 in long-term PD, notably with UFF make it worthwhile to be routinely measured, in order to clarify its predictive value. It was not the purpose of this study to investigate the relationship between mesothelial cell mass and peritoneal transport: an indirect role has recently been suggested but this seems to vary in short-and long-term PD, possibly mediated earlier by production of vasoactive factors [32][33][34] or later trough epithelial-mesenchymal transition [35] .…”
Section: Discussionmentioning
confidence: 99%
“…If one does a simple calculation of appearance rates comparing published rates in patients (which are remarkably similar between studies) with those of Bręborowicz et al [6] and other in vitro studies, then the rate of production in vitro is some 10–30 times higher. Whilst measurements in different matrices (tissue culture medium vs. effluent) might explain a small difference, there are clearly differences between a clean in vitro setup and the uremic peritoneal cavity exposed to both glucose-based dialysis solutions and intercurrent or episodic inflammation.…”
Section: Ca125: Where Are We Now?mentioning
confidence: 74%
“…These data on the ‘regulation’ of secretion, however, were at odds with both pre-existing and subsequently produced data suggestive of induction of CA125 by pro-inflammatory cytokines [4, 5]. In the current issue, Bręborowicz et al fan the flames of this debate further by suggesting, based exclusively on in vitro data, that CA125 production by peritoneal mesothelial cells neither correlates with, nor is regulated by pro-inflammatory cytokines [6]. …”
Section: Ca125: a Marker Of Mesothelial Cell Mass In Pd Patients?mentioning
confidence: 98%
See 1 more Smart Citation